Regulation of enteric nervous system via sacral nerve stimulation in opioid-induced constipated rats - Wang, Liyun; Gharibani, Payam; Yang, Yi; Guo, Yu; Yin, Jieyun (Frontiers in Neuroscience, 2023)
Objectives: Sacral nerve stimulation (SNS) has been employed for treating constipation. However, its mechanisms involving enteric nervous system (ENS) and motility are largely unknown. In this study, we investigated the possible ENS involvement of SNS in treating Loperamide-induced constipation in rats. Methods: experiment-1 was designed to study the effects of acute SNS on whole colon transit time (CTT). In experiment-2, we induced constipation by Loperamide and then applied daily SNS or sham-SNS for one week. Choline acetyltransferase (ChAT), nitric oxide synthase (nNOS) and PGP9.5 in colon tissue were examined at the end of the study. Moreover, survival factors such as phosphorylated AKT (p-AKT) and Glial cell-derived neurotrophic factor (GDNF) were measures by immunohistochemistry (IHC) and western blot (WB). Key Results: 1) SNS with one set of parameters shortened CTT starting at 90min after phenol red administration (p<0.05). 2) While Loperamide induced slow transit constipation with a significant reduction in fecal pellet number and feces wet weight, daily SNS for a week resolved constipation. 3) Moreover, SNS was able to shorten whole gut transit time comparing to sham-SNS (p=0.01). 4) Loperamide reduced the number of PGP9.5 and ChAT positive cells, and downregulated ChAT protein expression and upregulated nNOS protein expression, whereas these detrimental effects were significantly reversed by SNS. 5) Furthermore, SNS increased expressions of both GDNF and p-AKT in colon tissue. 6) Vagal activity was reduced following Loperamide (p<0.01); yet SNS normalized vagal activity. Conclusion: SNS with appropriate parameters improves opioid-induced constipation and reversed the detrimental effects of Loperamide on enteric neurons possibly via the GDNF-PI3K/Akt pathway.